Oryginał - sobowtór. W stronę archeologii pierwowzoryzmu - Jazowski, Mariusz (Er(r)go. Teoria - Literatura - Kultura, 2004)
Mariusz Jazowski, Original – Double. Towards Archaeology of Archetypism The essay approaches the problem of human identity from the original – double perspective.